Evaluation of Geotechnical Properties of Soil at Selected Sites in Al-Nasiriya City - Abdulhussein, Maitham A. (Iraqi Journal of Science, 2024)
Soil index properties are used to calculate and determine the geotechnical properties of soils and then determine soil suitability for the construction of engineering projects. Most of the geotechnical properties of soil affect each other directly or indirectly, and these properties can be utilized as indicators to calculate other properties.In the present study, some soil index properties were used to identify the geotechnical properties of soil. According to the unified classification system for soil, most soils were classified as low and high plasticity hilt. In addition, the soils showed a medium to a high degree of expansion according to the values of the Atterberg limit and were generally considered inactive clay soil. Based on the Standard Penetration Test values, consistency index, and compression index, the soil was stiff to extremely stiff and had high to extremely high compressibility. Finally, the results showed the need for soil for some engineering works, such as stabilization and modification, before the construction of engineering projects.